AUTONOMOUS NAVIGATION AND ATTITUDE CONTROL OF SPACECRAFTS ON NEAR-EARTH CIRCULAR ORBITS - Germanovitch, Andronov Vladimir; Gennadievitch, Emelyanov Sergey (Journal of Applied Engineering Science, 2018)
The paper reviews existing methods of spacecraft navigation and attitude control on near-earth orbits, including the methods utilizing earth-based external trajectory measurement stations, global navigation satellite systems, inertial on-board navigation systems and star trackers. The proposed method is based on the obtaining and processing of a set of sky images on-board of a spacecraft that is moving along a near-earth circular orbit. Image processing results are used to find the coordinates, velocity and attitude of a space craft in inertial space.